Development of Health E-Booklets in HIV/AIDS Prevention for Padang State University Students - Elsa Yuniarti; Dwi Anggia; Debby Sinthania (Jurnal Penelitian Pendidikan IPA, 2024)
Human Immunodeficiency Virus (HIV) is an infectious disease, if we pay attention to the various characteristics of disease transmission, then the form of transmission from the agent is a very important form because the nature of this disease is more often endemic and spreads more easily in society. In Indonesia, the spread of HIV/AIDS occurs evenly in almost all provinces. The prevalence of HIV cases in the population aged 15 - 49 years has increased. This research aims to produce E-Booklet. This type of research is development research using a 4-D model. The development stage of this model starts from the define stage, design stage and develop stage. The instruments used in this development research were student, lecturer questionnaires and validation sheets E-Booklet by experts, as well as a practicality assessment sheet E-Booklet filled by students and lecturers. The research results show that E-Bookletvery valid with an average score of 86.01%. The practicality assessment of students in the field trial (group evaluation size) was with a score of 95.00% with very practical criteria, and the practicality assessment by the lecturer obtained a score of 93.00% with very practical criteria. Can be concluded that E-Booklet that has been developed is included in the very valid and very practical category.